A high-aluminum cover glass strengthening method and high-aluminum cover glass
By applying the time-domain finite difference method to perform numerical simulation in the two-step ionic strengthening process of high-aluminum cover glass, the optimal time range for the second step of chemical strengthening was determined, and the cumbersome experiments and safety hazards in the existing process were solved. The problem has achieved efficient and accurate glass reinforcement effect.
Patent Information
- Application Number
- CN202211105081.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-09
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2042-09-09
AI Technical Summary
The existing two-step ion strengthening process requires heavy preparation and characterization experiments to determine the test parameters, and the high temperature and toxicity of the molten salt pose a potential threat to the health of researchers.
The numerical simulation model of potassium ion diffusion process was established by the time domain finite difference method, and the numerical parameters of potassium ion diffusion in the two-step ion strengthening process were determined. The numerical simulation diagram of the potassium ion concentration distribution in the second step of chemical strengthening process was obtained through numerical simulation. , analyze and determine the optimal time range for the second step of chemical strengthening.
The tedious work in the two-step ion strengthening process is simplified, the efficiency and accuracy of the process are improved, the threat to researchers' health is reduced, and high-aluminum cover glass with excellent performance is prepared.
Smart Images

Figure CN116119944B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of glass preparation, and in particular to a high-aluminum cover glass strengthening method and a high-aluminum cover glass. Background Art
[0002] Many scholars at home and abroad have conducted detailed research on the process system of preparing high-aluminum cover glass by two-step ion strengthening process. The results show that the time of the first step of chemical strengthening treatment must be long enough to ensure that the glass obtains a sufficiently deep compressive stress layer (CaseDepth). Under the premise of ensuring the first step, the key factor in preparing two-strength glass is the control of ion exchange in the second step of chemical strengthening, especially the control of the time of ion exchange in the second step of chemical strengthening. However, determining the production of this process requires arduous preparation and characterization experiments. In addition, the high temperature and toxicity of molten salt also pose a potential threat to the health of researchers.
[0003] The finite-difference time-domain method is a method that meshes continuous time and space, and uses differences instead of differentials within the grid to decompose and solve differential equations. The use of the finite-difference time-domain method can effectively avoid complicated mathematical operations. By using the high-speed computing power of modern computers, the calculation process can be simulated very quickly and accurately. Although the finite-difference time-domain method is an approximate solution method, as long as the step size of time and space is small enough, the results of the calculation simulation can be infinitely close to the actual analytical solution.
[0004] Therefore, how to combine the finite-difference time-domain method with cover glass strengthening and reduce the tedious work of secondary strengthening through simulation results is a new topic. Summary of the invention
[0005] The purpose of the embodiments of the present invention is to provide a high-aluminum cover glass strengthening method and a high-aluminum cover glass, so as to at least solve the above-mentioned shortcomings of the existing two-step ion strengthening process.
[0006] In order to achieve the above object, the first aspect of the present invention provides a high aluminum cover glass strengthening method, the strengthening method is applied to a two-step ion strengthening process, the two-step ion strengthening process includes a first step of chemical strengthening and a second step of chemical strengthening, the strengthening method includes:
[0007] A numerical simulation model of potassium ion diffusion process was established based on the finite-difference time-domain method;
[0008] Determine the numerical parameters for potassium ion diffusion during the two-step ion enhancement process;
[0009] Bringing the determined numerical parameters into the numerical simulation model to perform numerical simulation, and obtaining a numerical simulation diagram of potassium ion concentration distribution during the second step of chemical strengthening;
[0010] The optimal time range for the second step of chemical strengthening is determined based on the numerical simulation diagram analysis.
[0011] The high-aluminum cover glass strengthening method provided by the present invention uses a time-domain finite difference method to determine the optimal time range for the second step of chemical strengthening in a two-step ion strengthening process. The overall process is simple and fast, and the time-domain finite difference method can perform calculation simulation quickly and accurately, thereby ensuring the accuracy of the calculation results.
[0012] Optionally, the numerical simulation model of the potassium ion diffusion process is established based on the finite difference time domain method, comprising:
[0013] Based on the finite-difference time-domain method, the continuous space and time in the potassium ion diffusion process are discretized and a one-dimensional diffusion equation is established.
[0014] Optionally, the one-dimensional diffusion equation is as follows:
[0015]
[0016] Where i represents the time of potassium ion exchange, j represents the position of potassium ion exchange, 1<j<N, N represents the number of diffusion regions, C i,j represents the potassium ion concentration at point j and time i, D i,j represents the potassium ion diffusion coefficient at point j and time i, Δt represents the simulation space, and Δx represents the time step.
[0017] The one-dimensional diffusion equation can accurately simulate the diffusion process of potassium ions, and the simulation calculation can be realized by simply entering the required parameters.
[0018] Optionally, the numerical parameters of the potassium ions include:
[0019] The time of the first step chemical strengthening, the potassium ion concentration after the first step chemical strengthening, the potassium ion concentration after the second step chemical strengthening, and the potassium ion diffusion coefficient during ion exchange during the second step chemical strengthening.
[0020] Optionally, the potassium ion concentration after the first step of chemical strengthening and the potassium ion concentration after the second step of chemical strengthening are measured by a scanning electron microscope equipped with an energy dispersive spectrometer.
[0021] A scanning electron microscope (SEM) is a large precision instrument used for high-resolution micro-area morphology analysis. It has the characteristics of large depth of field, high resolution, intuitive imaging, strong three-dimensional sense, wide magnification range, and the ability to rotate and tilt the sample to be tested in three-dimensional space. It is very suitable for observing the distribution of potassium ion concentration.
[0022] Optionally, the potassium ion diffusion coefficient during ion exchange in the second step of chemical strengthening is calculated using the Boltzmann equation, and the Boltzmann equation is as follows:
[0023]
[0024] Wherein, Cs represents the surface potassium ion concentration of the glass after the ion exchange is completed, C(x,t) represents the potassium ion concentration when the potassium ion diffusion position is x and the time is t; Dt represents the potassium ion diffusion coefficient at the time t.
[0025] Optionally, the numerical simulation is realized using MATLAB software. MATLAB is a common numerical calculation software with efficient numerical calculation and symbolic calculation functions, which can free users from complicated mathematical operation analysis, and has complete graphics processing functions to realize the visualization of calculation results and programming, and facilitate the display of calculation results.
[0026] Optionally, also include:
[0027] Based on the obtained optimal time range for the second step chemical strengthening, experimental verification was carried out to confirm the actual strengthening process parameters of the high-aluminum cover glass.
[0028] The second aspect of the present invention provides a high-aluminum cover glass prepared based on the strengthening method described in the first aspect, wherein the composition of the high-aluminum cover glass is: SiO2: 52-65%, Al2O3: 13-21%, Na2O: 4-12%, K2O: 0-2.5%, SO2: 100ppm-1000ppm, ZrO2: 1-5%, MgO: 2-8%, Li2O: 0.5-7%, and the above composition is measured by mass fraction.
[0029] Optionally, the temperature of the first step of chemical strengthening is 410-430° C., and the time is 180-240 min. The temperature of the second step of chemical strengthening is 390-410° C., and the time is between 15 min and 120 min.
[0030] Optionally, the mass percentage of sodium nitrate and potassium nitrate during ion exchange in the first step of chemical strengthening is (50%-100%):(0%-50%), and the mass percentage of sodium nitrate and potassium nitrate during ion exchange in the second step of chemical strengthening is (0%-20%):(100%-80%).
[0031] Optionally, the surface compressive stress value of the high-aluminum cover glass is above 870 MPa.
[0032] Optionally, the compressive stress depth of the high-aluminum cover glass is above 100 μm.
[0033] Optionally, the Vickers hardness of the high-aluminum cover glass is above 650 MPa.
[0034] The above technical scheme avoids the problem of needing to carry out complex and arduous preparation and characterization experiments to obtain test parameters in the process of manufacturing high-aluminum cover glass using a two-step ion strengthening process. The above technical scheme enables the experimental results to be carried out better and faster, and on this basis, a high-aluminum cover glass with better performance can be prepared.
[0035] Other features and advantages of the embodiments of the present invention will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] The accompanying drawings are used to provide a further understanding of the embodiments of the present invention and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the embodiments of the present invention, but do not constitute a limitation on the embodiments of the present invention. In the accompanying drawings:
[0037] Figure 1 It is a flow chart of a high-aluminum cover glass strengthening method provided by one embodiment of the present invention;
[0038] Figure 2 It is a schematic diagram of time and space discretization processing of a numerical simulation model provided by one embodiment of the present invention;
[0039] Figure 3 A schematic diagram of potassium ion concentration distribution and Boltzmann fitting thereof at 430° C. provided by an embodiment;
[0040] Figure 4 A numerical simulation diagram of potassium ion concentration distribution provided by an embodiment. DETAILED DESCRIPTION
[0041] The specific implementation of the present invention is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described here is only used to illustrate and explain the present invention, and is not used to limit the present invention.
[0042] Figure 1 1 is a flow chart of a high aluminum cover glass strengthening method provided by one embodiment of the present invention. Figure 1 As shown, an embodiment of the present invention provides a method for strengthening high-aluminum cover glass, the method comprising:
[0043] S1: A numerical simulation model of potassium ion diffusion process is established based on the finite-difference time-domain method.
[0044] The basic idea of the finite-difference time-domain method is to replace the first-order partial derivative of the field quantity in time and space with the central difference quotient, and to obtain the field distribution by recursively simulating the wave propagation process in the time domain. In this embodiment, the concentration distribution of potassium ions in the high-aluminum cover plate strengthened glass is basically consistent with its stress distribution law. In order to numerically simulate the potassium ion diffusion process, according to the finite-difference time-domain method, it is first necessary to discretize the continuous space and time in the potassium ion diffusion process. In the following, i and j are used to represent the time ordinal and space ordinal, respectively, and the diffusion time and diffusion area are divided into M and N intervals according to 0 t0 t1 titM T and 0 x0 x1 xj xN L, respectively.
[0045] Due to the uniformity of the diffusion process, it can be assumed that the potassium ion concentration at the same depth along the surface is consistent. Therefore, the three-dimensional diffusion problem can be simplified to a one-dimensional problem and directly described by the one-dimensional diffusion equation:
[0046]
[0047] The concentration of a point in the grid at the next moment can be determined by the concentration difference between the current moment and its two adjacent points and their diffusion coefficients; equation (1) can be derived as the following equation (2):
[0048]
[0049] Where i represents the time of potassium ion exchange, j represents the position of potassium ion exchange, 1<j<N, C i,j represents the potassium ion concentration at point j and time i, D i,j represents the potassium ion diffusion coefficient at point j and time i, Δt represents the simulation space, and Δx represents the time step.
[0050] S2: Determine the numerical parameters for potassium ion diffusion during the two-step ion enhancement process.
[0051] The numerical parameters that need to be determined include the potassium ion concentration after the first step of chemical strengthening, the potassium ion concentration after the second step of chemical strengthening, and the potassium ion diffusion coefficient during ion exchange during the second step of chemical strengthening.
[0052] Among them, the potassium ion concentration after the first step of chemical strengthening and the potassium ion concentration after the second step of chemical strengthening were measured by a scanning electron microscope with an energy spectrometer. The scanning electron microscope has the characteristics of large depth of field, high resolution, intuitive imaging, strong three-dimensional sense, wide magnification range, and the sample to be tested can be rotated and tilted in three-dimensional space. It is suitable for detecting potassium ion concentration.
[0053] The potassium ion diffusion coefficient is calculated by the Boltzmann equation (3), which is as follows:
[0054]
[0055] Wherein, Cs represents the surface potassium ion concentration of the glass after the ion exchange is completed, C(x,t) represents the potassium ion concentration when the potassium ion diffusion position is x and the time is t; Dt represents the potassium ion diffusion coefficient at the time t.
[0056] S3: The determined potassium ion concentration after the first step of chemical strengthening, the potassium ion concentration after the second step of chemical strengthening, and the potassium ion diffusion coefficient during ion exchange in the second step of chemical strengthening are brought into the numerical model, and numerical simulation is performed using MATLAB software. MATLAB software has efficient numerical and symbolic calculation functions, which can free users from complicated mathematical calculations and analysis, and has complete graphics processing functions. After numerical simulation using MATLAB software, a numerical simulation diagram of the potassium ion concentration distribution during the second step of chemical strengthening is obtained.
[0057] S4: Based on the numerical simulation diagram obtained in S3, the optimal time range for the second step of chemical strengthening is determined.
[0058] S5: Experimental verification is performed based on the obtained optimal time range for the second step chemical strengthening to confirm the actual strengthening process parameters of the high aluminum cover glass.
[0059] This embodiment also provides a high-aluminum cover glass prepared based on the strengthening method provided in this embodiment. In some feasible embodiments, the composition of the high-aluminum cover glass is: SiO2: 52%, Al2O3: 13%, Na2O: 4%, SO2: 100ppm, ZrO2: 1%, MgO: 2%, Li2O: 0.5%, and the above composition is measured in mass fraction.
[0060] In some feasible embodiments, the composition of the high-aluminum cover glass is: SiO2: 58%, Al2O3: 16%, Na2O: 8%, K2O: 1%, SO2: 500ppm, ZrO2: 2.5%, MgO: 4%, Li2O: 3.5%, and the above composition is calculated by mass fraction.
[0061] In some feasible embodiments, the composition of the high-aluminum cover glass is: SiO2: 65%, Al2O3: 21%, Na2O: 12%, K2O: 2.5%, SO2: 1000ppm, ZrO2: 5%, MgO: 8%, Li2O: 7%, and the above composition is calculated by mass fraction.
[0062] In some feasible embodiments, the temperature of the first step of chemical strengthening is 410-430°C, and the time is 180-240min, the temperature of the second step of chemical strengthening is 390-410°C, and the time is between 15min-120min; the mass percentage of sodium nitrate and potassium nitrate during ion exchange in the first step of chemical strengthening is (50%-100%): (0%-50%), and the mass percentage of sodium nitrate and potassium nitrate during ion exchange in the second step of chemical strengthening is (0%-20%): (100%-80%); the surface compressive stress value of the high aluminum cover glass is above 870MPa; the compressive stress depth of the high aluminum cover glass is above 100μm; the Vickers hardness of the high aluminum cover glass is above 650MPa.
[0063] A specific implementation example is given below.
[0064] 1. Establish a numerical simulation model, and discretize the continuous space and time based on the finite difference time domain method. i and j represent the time ordinal and space ordinal. The specific discretization results are as follows: Figure 2 shown.
[0065] 2. Determine the first step of chemical strengthening time: According to the first step of chemical strengthening time and performance parameters, the optimal strengthening temperature is 430 ° C, and the ion exchange time is 3 hours; the mass percentage of sodium nitrate and potassium nitrate in the first step of chemical strengthening ion exchange is 70:30, and the mass percentage of sodium nitrate and potassium nitrate in the second step of chemical strengthening ion exchange is 10:90.
[0066] Determine the potassium ion concentration after the first step of chemical strengthening, the potassium ion concentration after the second step of chemical strengthening, and the potassium ion diffusion coefficient during the second step of chemical strengthening: The potassium ion concentration after the first step of chemical strengthening and the potassium ion concentration after the second step of chemical strengthening were measured using a scanning electron microscope with an energy spectrometer. The specific results are shown in Table 1 below:
[0067] Table 1 Surface potassium ion concentration
[0068]
[0069] According to the measurement results, the boundary conditions are determined and normalized, that is, the boundary conditions of the second step ion exchange are:
[0070] C1=C N =C S =4.71 / 7.69=0.61.
[0071] Measurement and calculation of potassium ion diffusion coefficient:
[0072] From the Boltzmann equation The potassium ion concentration at 430°C and its Boltzmann fitting diagram are shown in the figure below: Figure 3 As shown, Figure 3 The ordinate Normalized Concentration represents the planned concentration, and the abscissa Depth represents the depth.
[0073] 3. Use MATLAB software for simulation calculations. The simulation space and time step sizes Δx and Δt are set to 0.1 μm and 0.5 respectively, and the surface concentration value C S and the internal solubility value Ci are 0.610 and 0 respectively. The simulation experimental time domain and space domain are {0 = t0 < t1 < t2 <... tm = T}, {0 = x0 < x1 < x2 <... xm = L}, where L = 120 μm, and T is set to 15 min, 30 min, 45 min, 1 h, 1.5 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h respectively. Simulate the ion exchange during the second-step chemical strengthening process at 400 °C, and assume that the diffusion does not depend on the constant of potassium ion concentration, to obtain the numerical simulation diagram of the potassium ion concentration distribution Figure 4 .
[0074] 4. Obtain the optimal time range for the second-step chemical strengthening: From Figure 4 it can be seen that as the exchange time of the second-step chemical strengthening increases, the position of the maximum value point migrates from the surface to the interior, enters the plateau period at about 1.5 h, migrates significantly in the reverse direction after 3 h, and returns to the surface at 6.25 h. Therefore, the appropriate treatment time for the optimal ion exchange in the simulation is between 15 min and 2 h. Figure 4 The ordinate Normalized Concentration represents the planned concentration, and the abscissa Depth represents the depth.
[0075] 5. Conduct performance verification based on the simulation results to find out the process parameters for the two-step ion strengthening of high-aluminum cover glass.
[0076] Testing method:
[0077] Use the FSM-6000 stress meter to measure the surface compressive stress and the stress layer compression depth of the above samples respectively. The surface compressive stress can be abbreviated as CS, and the stress layer compression depth can be abbreviated as DOL. Use a Vickers hardness tester to measure the surface hardness of the above samples, and use the four-point bending method to measure the flexural strength of the above samples. Finally, calculate the average value, and the obtained data are shown in Tables 2 and 3.
[0078] Use a universal testing machine to conduct a 4-point bending test on the samples. The test conditions are: upper / lower span 20 / 40 cm, downward pressing speed 10 mm / min, and rod diameter 6 mm.
[0079] Table 2 mainly illustrates the material formula with given components and contents, the compressive stress values, compressive stress depths and compressive stress curves, Vickers hardness and flexural strength obtained by different chemical strengthening methods, wherein Example 1 performs a single chemical strengthening; Examples 2-20 are all secondary chemical strengthenings, wherein Examples 2-5 are verified based on simulation results; Examples 6-8 are second strengthening times that are not within the preferred range of the present application; Examples 9-12 are secondary strengthening temperatures, times and solution ratios that are not within the preferred range of the present application, Tables 13-18 are first chemical strengthening temperatures, times and solution ratios that are not within the preferred range of the present application, and Tables 19-21 are first and second chemical strengthening temperatures and solution ratios that are within the preferred range of the present application.
[0080] The glass frits used in the series of experiments in Table 2 are calculated by mass fraction, and the specific composition is as follows:
[0081] SiO2: 52-65%, Al2O3: 13-21%, Na2O: 4-12%, K2O: 0-2.5%, SO2100ppm-1000ppm, ZrO2: 1-5%, MgO2-8%, Li2O: 0.5-7%.
[0082] Table 2 Examples 1-7
[0083]
[0084] Table 3 Examples 8-14
[0085]
[0086] Table 4 Examples 15-21
[0087]
[0088]
[0089] It can be seen from Table 2-4 that:
[0090] When Examples 2-5 meet the simulated secondary strengthening conditions, the strengthened products have very excellent chemical strengthening properties and good bending resistance; wherein the surface compressive stress of Example 5 is 1198MPa, the depth of DOL is 126μm, the bending strength is 724MPa, and the Vickers hardness is 634MPa, which has excellent scratch resistance and bending resistance; the performance of Example 8 is worse than that of Example 5, and the difference lies in the different time of the first strengthening; Example 1 is a single strengthening, and the CS, stress layer depth t, bending resistance and Vickers hardness of the strengthened product are relatively low; the first strengthening temperature, strengthening time, molten salt type ratio of Examples 8 and 12, and the second strengthening molten salt type, strengthening temperature, and strengthening time are all different from those of Example 5, and the strengthening effect and bending resistance, drop resistance, and crack resistance of the products are also greatly reduced; by adopting Examples 2-5, 19-21 of the strengthening process technology scheme of the present application, the above-mentioned related properties are significantly improved.
[0091] It can be seen that when the content of each component in the glass composition is determined, the strengthening methods falling within the scope of this application, especially the programmed temperature strengthening method, will produce unexpected technical effects in terms of the surface compressive stress value of the glass product, the depth of the stress layer, the integrity rate of the glass after falling, the anti-fracture performance, etc.
[0092] The optional embodiments of the present invention are described in detail above in conjunction with the accompanying drawings. However, the embodiments of the present invention are not limited to the specific details in the above embodiments. Within the technical concept of the embodiments of the present invention, the technical scheme of the embodiments of the present invention can be subjected to a variety of simple modifications, and these simple modifications all belong to the protection scope of the embodiments of the present invention. It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the embodiments of the present invention will not further describe various possible combinations.
[0093] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the embodiments of the present invention, they should also be regarded as the contents disclosed in the embodiments of the present invention.
Claims
1. A high-aluminum cover glass strengthening method, the strengthening method is applied to a two-step ion strengthening process, the two-step ion strengthening process includes a first step of chemical strengthening and a second step of chemical strengthening, characterized in that: The second step chemical strengthening time is determined according to the following method: A numerical simulation model of potassium ion diffusion process was established based on the finite-difference time-domain method; Determine the numerical parameters for potassium ion diffusion during the two-step ion enhancement process; Bringing the determined numerical parameters into the numerical simulation model to perform numerical simulation, and obtaining a numerical simulation diagram of potassium ion concentration distribution during the second step of chemical strengthening; Determine the optimal time range for the second step of chemical strengthening based on the numerical simulation diagram analysis; Wherein, the numerical simulation model of potassium ion diffusion process is established based on the finite difference time domain method, including: Based on the finite-difference time-domain method, the continuous space and time in the potassium ion diffusion process are discretized and a one-dimensional diffusion equation is established. Wherein, the one-dimensional diffusion equation is as follows: Among them, i represents the time during potassium ion exchange, j represents the position during potassium ion exchange, 1 < j <N, where N represents the number of diffusion regions; represents that the position is j point and the time is i point, the potassium ion concentration at that time; represents that the position is point and the time is i point, the potassium ion diffusion coefficient at that time; represents the time step, represents the space for simulating potassium ion diffusion; Wherein, the numerical parameters of potassium ion diffusion include: The time of the first step chemical strengthening, the potassium ion concentration distribution after the first step chemical strengthening, the potassium ion concentration distribution after the second step chemical strengthening, and the potassium ion diffusion coefficient during ion exchange during the second step chemical strengthening; The potassium ion diffusion coefficient during ion exchange in the second step of chemical strengthening is calculated using the Boltzmann equation, which is as follows: in, It indicates the surface potassium ion concentration of glass after the ion exchange is completed; C (x, t) represents the potassium ion concentration when the potassium ion diffusion position is x and the time is t; D t represents the potassium ion diffusion coefficient at time t.
2. The high aluminum cover glass strengthening method according to claim 1, characterized in that: Also includes: Based on the obtained optimal time range for the second step chemical strengthening, the process parameters are verified to confirm the actual strengthening process parameters of the high-aluminum cover glass.
Citation Information
Patent Citations
Method for enhancing scratch resistance of lithium-aluminum-silicon glass
CN113213775A
Lithium aluminum silicate glass and preparation method thereof
CN114212996A